Needs and Problem of Health Insurance in India (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2022)
A premium, which can be paid in advance by a person or a group, can be used to purchasehealth insurance. The goal is to assist individuals obtain better access to healthcare. For bothindividuals and corporations, Indian insurance companies provide a wide range of products,including health insurance. Looking at factors such as infant mortality, maternal mortality, lifeexpectancy, and the number of live births and deaths can tell you a lot about a country's overallhealth. Although India has achieved great strides since its independence, there are still someconcerns with health insurance in the country. The study concluded that health insurance in Indiahas both advantages and disadvantages.